The Impact of International Tourism on Environmental Quality (Case Study: D8 Countries) - Roohollah Babaki; Behnam Elyaspour; Narges Sanjari Konarsandal (محیط زیست و توسعه فرابخشی)
Introduction: The problem of environmental degradation is one of the important global issues that is caused by human actions and activities. This issue is also of great importance from an economic point of view. Environmental degradation is not the result of a single factor or variable, and several causes and factors are involved in its emergence. This study addresses some of these factors, including tourism, economic growth, and urbanization.Materials and Methods: The main objective of the present study is to investigate the relationship between tourism, economic growth, urbanization, and environmental degradation in developing Islamic countries (including Iran, Turkey, Pakistan, Bangladesh, Indonesia, Malaysia, Egypt, and Nigeria) during the period 2005-2020 using the methods of Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), and Pooled Mean Group (PMG). The general model of this study is as follows:                                                                         CO2it = f (TRit, GDPit, POPit, Urit) Where CO2 is the amount of carbon dioxide emissions, TR is the income from arrival tourists (as a percentage of GDP), GDP is the economic growth rate, POP is the population growth rate, and UR is urbanization. It should be noted that the statistics and information required in this study were collected from the World Bank data source.Results: The results of this study, based on the findings from the model estimation using the Pooled Mean Group (PMG) method, show that the coefficient of the international tourism variable is significant at the one percent level and has a direct relationship with the carbon dioxide emission variable in eight developing Islamic countries. According to the results of this study, economic growth at the one percent level has a positive and significant relationship with the carbon dioxide emission variable in eight developing Islamic countries. Also, according to the results of the present study, urbanization at the one percent level has a positive and significant relationship with the carbon dioxide emission variable in eight developing Islamic countries. In addition, the results of this study indicate a positive and significant effect of population on carbon dioxide emissions in eight developing Islamic countries at the level of one percent; meaning that population growth reduces environmental quality in eight developing Islamic countries including Iran. Also, to examine the validity of the PMG model results, the model was estimated using two methods: DOLS and FMOLS, and their results confirm the validity of the model results estimated using the PMG method.Discussion: In summary, based on the results of this study, the coefficients of the variables of international tourism, economic growth, population, and urbanization are significant at the one percent level and have a direct relationship with the carbon dioxide emission variable. Meaning that an increase in each of these variables reduces environmental quality in eight developing Islamic countries including Iran. Therefore, it is suggested that, first, policymakers of international tourism destinations should adopt strategies that help these destinations reduce the use of fossil fuels and attract more tourism investments. Secondly, to improve environmental quality or reduce environmental degradation, instead of environmentally destructive diesel-powered transportation, tourist transportation with environmentally friendly vehicles such as electric vehicles and bicycle tourism should be selected and promoted in tourist destinations. Thirdly, carbon pricing approaches should be adopted that, like carbon taxes, not only facilitate emission reductions but can also provide an additional source of revenue.